Dostrzec i zrozumieć. Porównanie wybranych metod wizualizacji danych ALS wykorzystywanych w archeologii - Kiarszys, Grzegorz; Banaszek, Łukasz (Folia Praehistorica Posnaniensia, 2018)
Application of airborne laser scanning (ALS) for archaeological purposes allows for identification of relief features. Unless the detection is automated, the recognition of archaeological objects in the observed dataset is bounded by the interaction between human mind, eye and visual phenomena that are displayed on the screen. To improve effectiveness of ALS interpretation several visualization techniques have been developed. However, due to their complexity the spatial information produced by these algorithms differs. The aim of the paper is to present the discrepancies between the most popular visualization techniques used for archaeological purposes. Unlike previous attempts, the presented comparison is based on the vector outputs of the interpretative mapping. Therefore, we demonstrate in detail the differences in the morphology as well as quantity of identified archaeological features due to the use of various visualization techniques.